Tree diversity mitigates defoliation after a drought‐induced tipping point - Sousa‐Silva, Rita; Verheyen, Kris; Ponette, Quentin; Bay, Elodie; Sioen, Geert; Titeux, Hugues; Van de Peer, Thomas; Van Meerbeek, Koenraad; Muys, Bart (Global change biology, 2018)
Understanding the processes that underlie drought‐related tree vitality loss is essential for anticipating future forest dynamics, and for developing management plans aiming at increasing the resilience of forests to climate change. Forest vitality has been continuously monitored in Europe since the acid rain alert in the 1980s, and the intensive monitoring plots of ICP Forests offer the opportunity to investigate the effects of air pollution and climate change on forest condition. By making use of over 100 long‐term monitoring plots, where crown defoliation has been assessed extensively since 1990, we discovered a progressive shift from a negative to a positive effect of species richness on forest health. The observed tipping point in the balance of net interactions, from competition to facilitation, has never been reported from real ecosystems outside experimental conditions; and the strong temporal consistency of our observations with increasing drought stress emphasizes its climate change relevance. Furthermore, we show that higher species diversity has reduced the severity of defoliation in the long term. Our results confirm the greater resilience of diverse forests to future climate change‐induced stress. More generally, they add to an accumulating body of evidence on the large potential of tree species mixtures to face manifold disturbances in a changing world. Annual trends in plot‐averaged defoliation of trees along a tree species richness gradient in temperate deciduous forests.